Actualizing Disability Rights Under Law Number 8 of 2016: An Inclusive Development in Lheu Eu Village - Anzari, Mudhafar; Ikhwan, M.; Syukriah, Syukriah (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
The village, as a legal construct, comprises both a governing body and its community members. However, development initiatives in these rural areas often fail to meet the needs of individuals with disabilities. This neglect leads to the marginalization of persons with disabilities, forcing them to live in isolation within rural environments. In response, the Government of Indonesia has enacted Law No. 8 of 2016 concerning Persons with Disabilities. This legislation aims to elevate the status of persons with disabilities to that of equal citizens, ensuring fair rights and opportunities for their active participation in village development. This study employs a normative juridical methodology by analyzing data from legal documents and literature, complemented by an empirical approach through interviews with relevant stakeholders. The research seeks to elucidate the rights of persons with disabilities within the framework of village development and to explore village government perspectives on their inclusion. Development efforts must shift toward a community-centered model that integrates the interests of the disabled population. Accordingly, the welfare of persons with disabilities in Lheu Eu Village, Darul Imarah District, Aceh Besar, must be grounded in humanitarian principles. Collaborative efforts among village government, the business sector, academia, and disability advocates are essential to realizing the legal mandate and regulatory framework that govern the inclusion of persons with disabilities in rural development.